2010
DOI: 10.1016/j.physleta.2010.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Paraxial spin transport using the Dirac-like paraxial wave equation

Abstract: In weakly inhomogeneous media, Maxwell equations assume a Dirac-like form that is particularly apt for the study of paraxial propagation. Using this form, and via the Foldy-Wouthuysen transformation technique of the Dirac equation, we study the spin transport of paraxial light beams in weakly inhomogeneous media. We derive the Berry effect terms and establish the spin Hall effect and the Rytov rotation law for polarized paraxial beam transport.PACS numbers: 03.65. Vf,42.25.Bs,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…E bem sabido que aóptica e a mecânica quântica tem muito em comum [9][10][11][12][13][14][15][16][17][18][19][20][21] e as referências colocadas aqui nesse trabalho estão longe de encerrar todo o assunto. Do ponto de vista histórico uma formulação antiga baseada naóptica por Hamilton e Jacobi inspirou Erwin Schrödinger a escrever a versão ondulatória da mecânica quântica [8].…”
Section: Analogias Com a Mecânica Quânticáunclassified
“…E bem sabido que aóptica e a mecânica quântica tem muito em comum [9][10][11][12][13][14][15][16][17][18][19][20][21] e as referências colocadas aqui nesse trabalho estão longe de encerrar todo o assunto. Do ponto de vista histórico uma formulação antiga baseada naóptica por Hamilton e Jacobi inspirou Erwin Schrödinger a escrever a versão ondulatória da mecânica quântica [8].…”
Section: Analogias Com a Mecânica Quânticáunclassified
“…Historically, the analogy between Maxwell equations and those used in the relativistic electron theory has been discussed in different contexts and for various purposes (see, for example, 47,[92][93][94] ) since 1907 when Maxwell equations were reduced 95 to an alternative, more concise form by introducing a complex field F = E + iH:…”
Section: B Charge Transport In Disordered Graphenementioning
confidence: 99%
“…Indeed, many features of Anderson localization can be found in random graphene systems. It has been shown in 94 that although the wave functions of normally incident (θ = 0) particles are extended and belong to the continuous part of the spectrum, away from some vicinity of θ = 0, 1-D random graphene systems manifest all features of disorder-induced strong localization. In particular, for a long enough, disordered graphene superlattice the transmission coefficient, T , as a function of the angle of incidence, θ, (or of the energy E, if θ = 0 is fixed) has typical for Anderson localization shape, Fig.…”
Section: B Charge Transport In Disordered Graphenementioning
confidence: 99%
“…An "electric" field can be obtained through the definition E = −∇ ⊥ A 0 , making Eqs. (11) and (12) resemble Newton's second law for a "charged" particle, as follows:…”
Section: "Gauge" Symmetries Of the Optical Fieldsmentioning
confidence: 99%
“…In another research direction, the similarity of equations describing electromagnetic field propagation in optical frequencies with their analog of quantum mechanics suggests use of the former to simulate the behavior of the latter in a more or less classical way. For instance, one can consider M. Mehrafarin and H. Balajany, who showed that Maxwell's * cadartora@eletrica.ufpr.br equations assume a Dirac-like form, making the study of paraxial propagation easier in a weakly inhomogeneous medium [11].…”
Section: Introductionmentioning
confidence: 99%